2019
DOI: 10.1161/jaha.118.011801
|View full text |Cite
|
Sign up to set email alerts
|

Lung‐Derived SOD3 Attenuates Neurovascular Injury After Transient Global Cerebral Ischemia

Abstract: Background-Systemic innate immune priming is a recognized sequela of post-ischemic neuroinflammation and contributor to delayed neurodegeneration. Given mounting evidence linking acute stroke with reactive lung inflammation, we asked whether enhanced expression of the endogenous antioxidant extracellular superoxide dismutase 3 (SOD3) produced by alveolar type II pneumocytes would protect the lung from transient global cerebral ischemia and the brain from the delayed effects of ischemiareperfusion. Methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…We have previously shown that hSOD3 limits PMN activation in response to 3VO-induced ischemia alone. 44 Consistent with these results, flow analyses confirmed that focal SOD3 expression within the lung in TgSOD3 mice reduced expression of the activation marker CD11b relative to WT controls (TgSOD3 MFI: 25,906 vs. WT MFI: 45,064 for 10,000 events) in response to combined 3VO/LPS treatment (Fig. 1D).…”
Section: Hsod3 Lung Expression Protects Against 3vo/lpsinduced Lung Injurysupporting
confidence: 81%
“…We have previously shown that hSOD3 limits PMN activation in response to 3VO-induced ischemia alone. 44 Consistent with these results, flow analyses confirmed that focal SOD3 expression within the lung in TgSOD3 mice reduced expression of the activation marker CD11b relative to WT controls (TgSOD3 MFI: 25,906 vs. WT MFI: 45,064 for 10,000 events) in response to combined 3VO/LPS treatment (Fig. 1D).…”
Section: Hsod3 Lung Expression Protects Against 3vo/lpsinduced Lung Injurysupporting
confidence: 81%
“…A score of two is considered normal for each domain, with a maximum total score of 12. Assessments were performed 1 day before and/or 2 days after the BCCAO operation ( Mai et al, 2019 ; Supplementary Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ischemic stroke has pervasive effects outside the CNS, leading to a cascade of inflammatory events that drives multiorgan dysfunction and hampers long-term stroke recovery. Peripheral organs, such as the lung (Mai et al, 2017(Mai et al, , 2019, heart (Bieber et al, 2017), and intestine (Singh et al, 2016;Stanley et al, 2016), are particularly susceptible to stroke-induced injury and inflammation. For example, stroke increases the permeability of intestinal barriers (Singh et al, 2016;Stanley et al, 2016), alters bacterial composition of the gut, causing gut dysbiosis (Houlden et al, 2016;Singh et al, 2016), and promotes seeding of gut bacteria within the lung, spleen, and liver (Stanley et al, 2016).…”
mentioning
confidence: 99%